A revision of the subgenus Parasphingonotus Benediktov & Husemann, 2009 (Orthoptera: Oedipodinae: Sphingonotini) - Husemann, Martin; Ray, Jesse; Hochkirch, Axel (Zootaxa, 2011)
The recently erected subgenus Parasphingonotus is revised. The diagnostic characters are given and the species Sphingonotus (Parasphingonotus) radioserratus comb. n., Sphingonotus (Parasphingonotus) femoralis comb. n. and Sphingonotus (Parasphingonotus) turkanae comb. n. are assigned to the subgenus. Sphingonotus (Parasphingonotus) airensis is synonymized with S. (P.) femoralis, making the latter species the new type species of Parasphingonotus. Keys to the subgenera (Sphingonotus, Neosphingonotus, and Parasphingonotus) of the genus Sphingonotus and to the species of Parasphingonotus are presented. All Parasphingonotus species are re-described and further information on the distribution of the species are given.